PEMANFAATAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS CERPEN MELALUI MODEL PEMBELAJARAN KREATIF PRODUKTIF - SRI INDRIYATI (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2021)
This study aims to describe the results of the ability to write short stories by utilizing serial image media through product creative learning models for class IX students at MTs Negeri 2 Banyumas. From the results of the initial conditions of learning to write short stories before using the media, it was found that the average ability of students in writing short stories was still far from the specified Minimum Completeness Criteria (KKM), which was a score of 72 and above. There are still many students who have not scored 72, which is 41.20%, while those who scored 72 and above are 58.22%. The inability of students to achieve this KKM requires an innovation, namely the use of serial image media through productive creative learning methods in learning to write short stories. So that there is an increase in the value of the results of writing short stories made by students using serial images, namely; the average ability to write short stories of students has increased from before when viewed from the percentage of previous learning outcomes, after using serial image media through productive creative learning methods, the results of learning to write short stories increased to 82.35%. From these results, it can be seen that there are still 17.65% of students who still get a score below 72, while others get a score of 72 and above. This proves that the use of serial image media through product creative learning methods can improve students' abilities in writing short stories. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan hasil kemampuan menulis teks cerpen dengan memanfaatkan media gambar berseri melalui model pembelajaran kreatif produk pada peserta didik kelas IX MTs Negeri 2 Banyumas. Dari hasil kondisi awal pembelajaran menulis teks cerpen sebelum menggunakan media ditemukan bahwa kemampuan rata-rata peserta didik dalam menulis cerpen masih jauh dari Kriteria Ketuntasan Minimum (KKM) yang ditetapkan, yaitu nilai 72 ke atas. Masih banyak peserta didik yang belum mendapat nilai 72 yaitu 41,20% sedangkan yang mendapat nilai 72 ke atas sebanyak 58,22%. Ketidakmampuan peserta didik dalam mencapai KKM ini membutuhkan sebuah inovasi, yaitu penggunaan media gambar berseri melalui metode pembelajaran kreatif produktif dalam pembelajaran menulis teks cerpen. Sehingga ada peningkatan nilai dari hasil menulis teks cerpen yang dibuat peserta didik dengan menggunakan media gambar berseri yaitu; rata-rata kemampuan menulis teks cerpen peserta didik sudah meningkat dari sebelumnya apabila dilihat dari prosentase hasil belajar sebelumnya, setelah menggunakan media gambar berseri melalui metode pembelajaran kreatif produktif hasil pembelajaran menulis teks cerpen meningkat menjadi 82,35%. Dari hasil tersebut dapat diketahui masih ada 17,65% peserta didik yang masih mendapatkan nilai di bawah 72, sedangkan lainnya mendapat nilai 72 ke atas. Hal ini membuktikan bahwa penggunaan media gambar berseri melalui metode pembelajaran kreatif produk dapat meningkatkan kemampuan peserta didik dalam menulis teks cerpen.